Immediate environmental impacts of transformation of an oil palm intercropping to a monocropping system in a tropical peatland - Dhandapani, Selva; Girkin, Nicholas T.; Evers, Stephanie; Ritz, Karl; Sjögersten, Sofie (International Mire Conservation Group, International Peat Society, 2022)
The expansion of oil palm plantations is one of the greatest threats to carbon-rich tropical peatlands in Southeast Asia. More than half of the oil palm plantations on tropical peatlands of Peninsular Malaysia are smallholder-based, which typically follow varied cropping systems, such as intercropping. In this case study, we compare the immediate biogeochemical impacts of conversion of an oil palm and pineapple intercropping to an oil palm monocropping system. We also assess how these changes affect the subsequent temperature sensitivity of greenhouse gas (GHG) production. We found that peat bulk density is unchanged, while organic matter content, pH and temperature is slightly yet significantly altered after conversion from oil palm intercropping to monocropping. Both in-situ and ex-situ CO2 emissions and temperature sensitivity of CO2 and CH4 production did not significantly vary between conversion stages; however, in-situ CO2 emissions in monocropping system exhibited a unique positive correlation with moisture. The findings show that some of the defining peat properties, such as bulk density and organic matter content, were mostly conserved immediately after conversion from intercropping to oil palm monocropping. However, there were signs of deterioration in other functional relationships, such as significantly greater CO2 emissions observed in the wet season to that of the dry season, showing moisture limitation to CO2 emissions in monocropping, postconversion. Nevertheless, there is a need for further research to identify the long-term impacts, and also the sustainability of intercropping practices in mature oil palm plantations for the benefit of these peat properties.
Keywords: carbon dioxide; methane; oil palm intercropping; temperature sensitivity; tropical peat